Overweight and obesity among school-aged adolescents in Yaounde (Cameroon) - Leslie B, Simomia Mbowen; HB, Nguendo Yongsi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introduction Overweight and obesity are a major public health problem due to its association with serious chronic diseases. Concerning childhood overweight/obesity, its rise in developing countries is so that there is a need to provide more evidence on its burden and associated factors in order to set preventive measures. Methods This study was designed to know the prevalence and related factors of overweight and obesity amongst adolescents in Yaoundé- Cameroon, and to draw their epidemiological profile. Results The prevalence of overweight and obesity was 13.6% and 4.3% respectively. Results revealed that practices associated with overweight and obesity are increase in age (R = 0.42, p < 0.001), female gender (p < 0.001). In addition, the use of bikes, cars or buses to go to school compared to walking (OR: 0.26; CI: 0.14 – 0.64; p = 0.0026) increase the risk of being overweight or obese. After adjusting the multivariable logistic model for age and sex with our study variables, it reveals that the odds of being obese for those who consume alcohol once a week were nine fold higher than that of those who consumed 2-5 times a week (OR: 9.37; CI: 1.34 to 193.41). Conclusions This results show that there is a need for health education in schools so as to help in health promotion and prevention, therefore avoid chronic disease conditions at older ages.